Formal Techniques for Distributed Systems Joint 12th IFIP WG 6.1 International Conference, FMOODS 2010 and 30th IFIP WG 6.1 International Conference, FORTE 2010, Amsterdam, The Netherlands, June 7-9, 2010. Proceedings - Hatcliff, John.; Zucca, Elena; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 12th IFIP WG 6.1 International Conference on Formal Methods for Open Object-Based Distributed Systems, FMOODS 2010, and the 30th IFIP WG 6.1 Formal Techniques for Networked and Distributed Systems, FORTE 2010, held in Amsterdam, The Netherlands, in June 2010. The 13 revised full papers presented together with 6 short papers and the abstract of one invited talk were carefully reviewed and selected from 38 submissions. The papers are organized in topical sections on formal UML modeling; components and architecture; timed process algebra; timed and hybrid automata; program logics and analysis; and reasoning about distributed systems.
Invited Talk -- Formal Software Verification: How Close Are We? -- Formal UML Modeling -- Exploiting the Hierarchical Structure of Rule-Based Specifications for Decision Planning -- Reactive Semantics for Distributed UML Activities -- Components and Architecture -- Statistical Abstraction and Model-Checking of Large Heterogeneous Systems -- Formal Semantics and Analysis of Behavioral AADL Models in Real-Time Maude -- Testing Probabilistic Distributed Systems -- Specification and Testing of E-Commerce Agents Described by Using UIOLTSs -- Testing Attribute-Based Transactions in SOC -- Joint DisCoTec Session -- Grouping Nodes in Wireless Sensor Networks Using Coalitional Game Theory -- Timed Process Algebra -- Forgetting the Time in Timed Process Algebra -- Theory and Implementation of a Real-Time Extension to the ?-Calculus -- Timed and Hybrid Automata -- Fuzzy-Timed Automata -- Model Checking of Hybrid Systems Using Shallow Synchronization -- Program Logics and Analysis -- Heap-Dependent Expressions in Separation Logic -- Static Type Analysis of Pattern Matching by Abstract Interpretation -- Reasoning about Distributed Systems -- On-the-Fly Trace Generation and Textual Trace Analysis and Their Applications to the Analysis of Cryptographic Protocols -- On Efficient Models for Model Checking Message-Passing Distributed Protocols -- Logics for Contravariant Simulations.
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Computer Science; Computer Communication Networks; Programming Techniques; Software Engineering; Programming Languages, Compilers, Interpreters; Logics and Meanings of Programs; Mathematical Logic and Formal Languages